Poškodbe glave zaradi smučanja, drsanja, kotalkanja ali deskanja na snegu in preprečevanje teh poškodb z uporabo čelade - Grmek-Košnik, Irena (Zdravstveno varstvo, 2008)
Background: Injuries are the third cause of death in Slovenia, with head trauma as the most frequent type of injury. Falls are the most common external cause of fatal intracranial injury. Because of their serious consequences, accidental brain injuries present significant challenges to the society. Head injuriesdue to a fall while skiing, skating, roller skating and snowboarding (SSRSSB) were studied. Methods: We analysed national health statistics data on mortality rate, emergency clinic visits, hospital admissions and rehabilitation of patients in Slovenia between 1997 and 2004. The SPSS programme was used for statistical analysis. Mortality rates, emergency clinic visits and first hospitalisation rates were calculated on thebasis of data on permanent residents of Slovenia during the period 1997 - 2004 provided by the central population register of the Republic of Slovenia. Results: During the eight-year period (1997 - 2004), 2,445 deaths due to head injuries were reported (individual years: 14.0 - 17.3 per 100,000 population).Seven deaths (0.3%) were due to SSRSSB-related falls (0.05 - 0.1 per 100,000 population). Between 1999 and 2004, 75,633 visits to emergency clinics because of head injuries were reported (individual years: 529 - 708 per 100,000 population). A total of 456 individuals (0.6%) attended because ofhead injury resulting from SSRSSB-related falls (2.1 - 5.2 per 100,000 population). During the period 1997 - 2004, 64,182 first in-hospital treatments for head trauma were recorded (366 - 424 per 100,000 population); 1,014 (1.6%) of these were given to patients with head injury resulting from aSSRSSB-related fall (4.5 - 8.7 per 100,000 population). The following fall-induced head injuries related to SSRSB were treated in hospital: 674 skull injuries (S06), 219 superficial head injuries (S00), 87 skull and facialbones fractures (S02), 30 head wounds (S01), three eye and orbit injuries and one injury from other causes (S03). Total length of hospital stayfor all patients with SSRSB-related head trauma was 3,180 days; the average hospital stay was 3.1 days. Conclusions:ßevere, even fatal fall-induced head injuries associated with SSRSSB, which are an important public health issue in Slovenia, may be prevented by carrying a helmet. There is a need to intensify promotional activities to encourage helmet use by SSRSSB participants. Article 12 of the "Safety on Ski Slopes Act" stipulates that ski helmet use is compulsory for all children under 12 years: we proposethat the age should be raised to a minimum of 14 years, like in the neighbouring countires. Moreover, we strongly recommend the use of a protective helmet to all SSRSSB participants whatever their age.
Keywords: čelada; deskanje; drsanje; glava; poškodbe; predpisi; preprečevanje; rolanje; smučanje; športne poškodbe; vzroki